Distribution and phylogenetics of whiteflies and their endosymbiont relationships after the Mediterranean species invasion in Brazil - de Moraes, Letícia Aparecida [UNESP]; Muller, Cristiane; Bueno, Regiane Cristina Oliveira de Freitas [UNESP]; Santos, Antônio; Bello, Vinicius Henrique [UNESP]; De Marchi, Bruno Rossitto [UNESP]; Watanabe, Luís Fernando Maranho [UNESP]; Marubayashi, Julio Massaharu [UNESP]; Santos, Beatriz Rosa [UNESP]; Yuki, Valdir Atsushi; Takada, Hélio Minoru; de Barros, Danielle Ribeiro; et al. (Springer Nature, 2018)
The Bemisia tabaci is a polyphagous insect and a successful vector of plant viruses. B. tabaci is a species complex and in Brazil native species from the New World (NW) group, as well as the invasive species, Middle East-Asia Minor 1 (MEAM1) and Mediterranean (MED) were reported. For better understanding the distribution of the different species four years after the Mediterranean species invasion in Brazil, whiteflies were collected from 237 locations throughout the country between the years of 2013 and 2017, species were identified and the facultative endosymbionts detected. The survey revealed that MEAM1 was the prevalent species found on major crops across Brazil. It is the only species present in North, Northwestern and Central Brazil and was associated with virus-infected plants. MED was found in five States from Southeast to South regions, infesting mainly ornamental plants and was not associated with virus-infected plants. The prevalent endosymbionts identified in MEAM1 were Hamiltonella and Rickettsia; and the mtCOI analysis revealed low genetic diversity for MEAM1. In contrast, several different endosymbionts were identified in MED including Hamiltonella, Rickettsia, Wolbachia and Arsenophonus; and two distinct genetic groups were found based on the mtCOI analysis. Monitoring the distribution of the whiteflies species in Brazil is essential for proper management of this pest.